Comparison of ABO Blood Group Antibody Titers in Elderly and Young Adult Patients - Dianawati, Dina Asri; Lismayanti, Leni; Wasilah, Fajar (Faculty of Medicine, Universitas Padjadjaran, 2025)
Immunosenescence in the elderly decreases their antibodies, which may lead to weaker degree of agglutination formation that potentially causes ABO discrepancies. This may lead to misinterpretation of blood group in this group. This study aimed to determine whether there are differences in antibody titer levels and degree of agglutination formed when examining ABO blood groups in the elderly as compared to young adults. This was a cross-sectional study employing analytical observational methods. Data were collected prospectively from the Blood Services Unit of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, between May 2022 and July 2022. The subjects included were 42 elderly participants and 42 young adults, grouped accordingly. The ABO blood typing was performed using the slide method, while anti-A and anti-B titers were measured by serial two-fold dilution using the tube method. A significant difference in ABO blood group antibody titer levels was observed between elderly and young adult groups (median: 6 vs 64, p<0.001). Antibody titers were lower in the elderly across blood groups A (median: 8 vs 64, p<0.001), B (median: 8 vs 64, p<0.001), and O (median: 4 vs 64, p<0.001). The degree of agglutination was lower in the elderly (2+) compared to young adults (4+). On average, antibody titers in elderly individuals were approximately tenfold lower than those in young adults across all three blood groups. The reduced degree of agglutination further supports the diminished antibody response in the elderly group.